Precise and Accurate Determination of Lu and Hf Contents, and Hf Isotopic Compositions in Chinese Rock Reference Materials by MC‐ICP‐MS. Issue 3 (18th May 2020) - Yang, Ming; Yang, Yue‐Heng; Evans, Noreen J.; Xie, Lie‐Wen; Huang, Chao; Wu, Shi‐Tou; Yang, Jin‐Hui; Wu, Fu Yuan
Abstract : In this contribution, we report Hf isotopic data and Lu and Hf mass fractions for thirteen Chinese rock reference materials (GBW07 103–105, 109–113 and 121–125, that is GSR 1–3, 7–11 and 14–18, respectively) that span a broad compositional range. Powdered samples were spiked with a 176 Lu‐ 180 Hf enriched tracer and completely digested using conventional HF, HNO3 and HClO4 acid dissolution protocols. Fluoride salts were dissolved during a final H3 BO3 digestion, and chemical purification was performed using a single Ln resin. All measurements were carried out on a MC‐ICP‐MS. This work provides the first comprehensive report of the Lu‐Hf isotopic composition of Chinese geochemical rock reference materials, and results indicate that they are of comparable quality to the well‐characterised and widely used USGS and GSJ rock reference materials. Key Points: Lu and Hf content, and Hf isotopic composition of 13 Chinese rock reference materials are reported for the first time. The reference materials span a broad compositional range. Results indicate that they are of comparable quality to the well characterised and widely utilised USGS and GSJ rock reference materials.